2018
DOI: 10.1080/21691401.2018.1533848
|View full text |Cite
|
Sign up to set email alerts
|

The specific RIP1 inhibitor necrostatin-1 ameliorated degradation of ECM in human SW1353 cells

Abstract: Abnormal destruction of the components of the articular extracellular matrix (ECM) such as type II collagen and aggrecan caused by advanced glycation end products (AGEs) has been considered as one of the pathological characteristics of osteoarthritis (OA). Receptor-interacting protein 1 (RIP1), an important serine/threonine kinase, possesses a variety of biological functions including cell proliferation, survival and death. The physiological roles of RIP1 in OA have not been reported before. Here, we found tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…To understand the link between HOTAIR and OArelated gene expression, we studied the effects of HOTAIR silencing and over-expression in chondrocytes by using SW1353 cells as an established chondrocytic cell model and a reliable transfection host [42]. Although SW1353 is a chondrosarcoma cell line, the cells exhibit similar responses as primary chondrocytes to a variety of catabolic cytokines relevant to OA, and have been used as the cell line of choice in many studies to investigate the molecular mechanisms of OA pathogenesis [43][44][45]. We found that HOTAIR over-expression in SW1353 cells matched the expression profile of OA-related genes in human primary osteoarthritic chondrocytes, characterised by the upregulation of catabolic enzymes (MMP-13, ADAMTS5) and cartilage repair markers (BMP-2), and downregulation of anabolic markers (TIMP3, SOX9) and cartilage matrix proteins (ACAN).…”
Section: Discussionmentioning
confidence: 99%
“…To understand the link between HOTAIR and OArelated gene expression, we studied the effects of HOTAIR silencing and over-expression in chondrocytes by using SW1353 cells as an established chondrocytic cell model and a reliable transfection host [42]. Although SW1353 is a chondrosarcoma cell line, the cells exhibit similar responses as primary chondrocytes to a variety of catabolic cytokines relevant to OA, and have been used as the cell line of choice in many studies to investigate the molecular mechanisms of OA pathogenesis [43][44][45]. We found that HOTAIR over-expression in SW1353 cells matched the expression profile of OA-related genes in human primary osteoarthritic chondrocytes, characterised by the upregulation of catabolic enzymes (MMP-13, ADAMTS5) and cartilage repair markers (BMP-2), and downregulation of anabolic markers (TIMP3, SOX9) and cartilage matrix proteins (ACAN).…”
Section: Discussionmentioning
confidence: 99%
“…However, current investigation on the physiological function of RIP in hypertrophic scars still requires exploring. A research has found that Nec‐1 inhibits degradation of ECM in osteosarcoma cells 9 . In addition, Nec‐1 decreases generation of TGF‐β and α‐SMA to alleviate renal fibrosis injury 10 …”
Section: Introductionmentioning
confidence: 99%
“…To elucidate the link between miR-1 expression and OA-associated gene transcription, we studied the effects of miR-1 over-expression and under-expression in chondrocytes by transfecting SW1353 cells with a miR-1 agonist and antagonist, respectively. Although SW1353 is a chondrosarcoma cell line with limited similarities in gene expression profile compared to primary human chondrocytes, they have similar responses as primary chondrocytes to catabolic cytokines such as IL-1β, and have been used in many studies to investigate protease expression and regulation in chondrocytic cells [34], or molecular mechanisms of pathogenesis in OA [35][36][37]. In our study, we chose SW1353 cells for use as a reliable transfection host that replicated some of the key characteristics of chondrocytic cells.…”
Section: Discussionmentioning
confidence: 99%